Asseessing the Efficacy of Interdiciplinary Curiculum Model in STEM Education: A Review - Ifa Safira; Dewanto; Suyahman; Everhard Markiano Solissa; Unpris Yastanti (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
STEM (Science, Technology, Engineering and Maths) education plays an important role in preparing students for the challenges of the 21st century. The interdisciplinary curriculum model, which integrates different STEM disciplines, has been proposed as an effective approach to enhance STEM learning.This research aims to evaluate the effectiveness of the Interdisciplinary Curriculum Model in STEM education through a comprehensive review. A literature search method was used to investigate various interdisciplinary approaches applied in the context of STEM education. The review investigated the benefits, challenges and implementation strategies associated with using interdisciplinary curriculum models in improving students' STEM understanding and skills. The results show that these model can increase students' motivation, engagement, and understanding of STEM concepts. The interdisciplinary model can also help students develop better problem-solving, critical thinking and collaboration skills. However, the effectiveness of the model may vary depending on factors such as implementation, curriculum design, and student characteristics. Further research is needed to identify factors that contribute to the effectiveness of this model and to develop better guidelines for its implementation. Overall, this review highlights the potential of interdisciplinary curriculum models to enhance STEM learning and provides important insights for educators and policymakers considering implementing these models in their schools.